Upaya Meningkatkan Aktivitas Dan Hasil Belajar IPA Dengan Menggunakan Pendekatan Contextual Teaching And Learning (CTL) Di Kelas III Sekolah Dasar - Sri Amerta (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
Learning science is supposed to link learning to real life, students actively seek and find their own knowledge and skills they need. Therefore, teachers should be able to choose the approach that suits the characteristics of science teaching, the approach provides an opportunity for students to discover themselves and in accordance with the real life of students. One approach that can be used is the approach of Contextual Teaching and Learning (CTL). CTL approach helps students to understand the meaning of the subject matter learned and the meteri associate with the context of their lives, so has the knowledge and skills that can be applied to solve problems encountered in everyday life. Thus, the learning process can improve the activity carried out and the results of student learning in science learning.